MODEL KONSEPTUAL HIDROGEOLOGI LAPANGAN PANASBUMI ‘AFH‘ KABUPATEN SALAHUTU, PROVINSI MALUKU DENGAN MENGGUNAKAN METODE GEOKIMIA AIR DAN GAS: HYDROGEOLOGICAL CONCEPTUAL MODEL OF 'AFH' GEOTHERMAL FIELD AT SALAHUTU REGENCY, MALUKU PROVINCE USING WATER AND GAS GEOCHEMISTRY METHODS - Adrian Febrianto Hanggoro; Fajar Hendrasto; Yudistian Yunis (Universitas trisakti, 2022)
The research area is a geothermal field located in the Tulehu area, Salahutu District, Maluku Province. The purpose of this research is to interpret the conceptual model of the geothermal system with the data that has been obtained. The first method is water geochemistry which includes ion balance, water type, water source, water geothermometer and water geoindicator. Theremore, the isotopic geochemical method is applied, which is to determine the source of the fluid. Then using gas geochemical methods including gas sources, gas geothermometers, and gas geoindicators. Based on the descriptive provisions, the research area is included in the low relief liquid dominated system. Based on the heat source, the research area is included in seawater. The research area is a medium temperature geothermal system with reservoir temperatures ranging from 185˚C to 240˚C with reservoir temperature parameters. Based on geological and geochemical interpretations, the upflow area in the study area is in the middle of the study area in the Hatuasa regionor between Mt. Salahutu and Mt. Erikawang, while the outflow area is in the eastern part of the study area, or towards the coastal line in Tulehu region